Implementation of Taxation in Village Fund Management in Sampulungan Village, North Galesong District, Takalar Regency - Muh. Asrullah Muslim (Pustaka Digital Indonesia, 2023)
The purpose of this study is to find out the implementation of taxation in managing village funds in Sampulungan village North Galesong district Takalar regency. The data used in this study is in the form of data sourced from the Sampulungan Village Government, namely the general treasury book. The data analysis technique used is a qualitative technique using data collection methods, data reduction, presentation of data and conclusions. The results of the research and discussion of the implementation of taxation in managing village funds in Sampulungan Village North Galesong District Takalar Regency, the researchers can draw conclusions that the implementation of this taxation shows that tax calculations in Sampulungan Village are in accordance with the provisions of the tax law. However, the village treasurer made delays in depositing and reporting VAT, Article 22 Income Tax and Article 23 Income Tax which were not in accordance with the tax law, due to delays in depositing and reporting taxes the village treasurer was subject to a fine. The village treasurer does not pay a fine for the delay so that he can be subject to sanctions in accordance with PMK of the Republic of Indonesia number 64/PMK.05/2013 article 17.